2020
DOI: 10.1183/23120541.00093-2019
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary tularaemia: a differential diagnosis to lung cancer

Abstract: BackgroundPulmonary manifestations of tularaemia are reported to be infrequent in previous publications. During 2016, we noticed an increase in the number of hospitalised patients with pulmonary tularaemia in Eastern Norway. We aimed to investigate primary pulmonary tularaemia in Eastern Norway in terms of symptoms, radiological and microbiological findings, incidence and risk exposure.MethodsA retrospective analysis of consecutive primary pulmonary tularaemia cases from 2016 until 2018 was conducted.ResultsFr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Our cohort had similar demographics to previous studies performed in northern Europe [ 3 , 9 , 11 , 28–31 ] and identified men and women aged 40 to 60 years as having the highest burden of tularemia, although there was high prevalence of infection throughout all age groups. Our data support ulceroglandular tularemia transmitted by mosquitos as the predominant clinical form in this geographical region [ 6 , 31 ], pulmonary tularemia as an important cause of pneumonia, and atypical disease often misdiagnosed as malignancy and/or tuberculosis [ 9 , 32 ]. Immunosuppression was infrequent in our cohort (n = 8), with 4 cases admitted to the hospital, including 1 developing pulmonary tularemia and 2 cases with F. tularensis septicemia.…”
Section: Discussionsupporting
confidence: 74%
“…Our cohort had similar demographics to previous studies performed in northern Europe [ 3 , 9 , 11 , 28–31 ] and identified men and women aged 40 to 60 years as having the highest burden of tularemia, although there was high prevalence of infection throughout all age groups. Our data support ulceroglandular tularemia transmitted by mosquitos as the predominant clinical form in this geographical region [ 6 , 31 ], pulmonary tularemia as an important cause of pneumonia, and atypical disease often misdiagnosed as malignancy and/or tuberculosis [ 9 , 32 ]. Immunosuppression was infrequent in our cohort (n = 8), with 4 cases admitted to the hospital, including 1 developing pulmonary tularemia and 2 cases with F. tularensis septicemia.…”
Section: Discussionsupporting
confidence: 74%
“…According to Kravdal et al, the most common routes of bacteria transmission are wood chopping, farming, carpentry, hunting, and other outdoor activities [49]. Most of the patients in this study became infected in the autumn.…”
Section: Clinical Manifestationsmentioning
confidence: 48%
“…Most cases present as subacute or chronic infections with relatively non-specific symptoms, including fever, cough, chest pain, and dyspnea. Radiological findings include hilar adenopathy, suggesting tuberculosis or non-infectious diseases (e.g., lymphoma, lung cancer, and sarcoidosis), lobar or multi-lobar infiltrates, and pleural effusion [41,49]. Most commonly, enlarged mediastinal or hilar lymph nodes and pulmonary lesions are found on the chest CT.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Hence, the seasonal increase in the incidence of tularaemia also correlates with tick bites 11 22. Infections by domestic animals through scratches or bites or the aerosolisation of rodents’ carcasses or excrements through activities such as lawn mowing, gardening or house renovations have been reported 17 23–26…”
Section: Discussionmentioning
confidence: 99%